2019
DOI: 10.1021/acs.inorgchem.9b00288
|View full text |Cite
|
Sign up to set email alerts
|

Structural Evolution and Compositional Modulation of ZIF-8-Derived Hybrids Comprised of Metallic Ni Nanoparticles and Silica as Interlayer

Abstract: Great efforts on metal−organic framework (MOF) derived nanostructures have been devoted to modulating the compositional and structural complexities to enhance performance in various applications. However, a facile method that can simultaneously manipulate the structures of the MOF-derived material and the chemical component remains a considerable challenge. Here we report a facile strategy to use the polyhedral ZIF-8 as a precursor for synthesizing ZIF-8-derived hybrids with different components and morphologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(36 citation statements)
references
References 55 publications
1
35
0
Order By: Relevance
“…The Langmuir equation assumes that during the adsorption process there is monolayer coverage of the adsorbates on the adsorbents with no interactions between the adsorbate molecules [30,31]. Previous studies reported the adsorption of PFOS on ACs followed the Langmuir model [19,20]; however, when comparing R 2 values, the Freundlich model fitted the adsorption of OBS on ACs better in the present study.…”
Section: Resultsmentioning
confidence: 64%
“…The Langmuir equation assumes that during the adsorption process there is monolayer coverage of the adsorbates on the adsorbents with no interactions between the adsorbate molecules [30,31]. Previous studies reported the adsorption of PFOS on ACs followed the Langmuir model [19,20]; however, when comparing R 2 values, the Freundlich model fitted the adsorption of OBS on ACs better in the present study.…”
Section: Resultsmentioning
confidence: 64%
“…Like reported in the previous adsorption studies, Langmuir adsorption isotherm was used to correlate the amount of metal ions adsorbed by unit mass of adsorbent where monolayer type coverage of metal ions is assumed over energetically identical adsorption sites of the adsorbent surface. The Langmuir model can be written as equation : true1boldqbolde=1boldqboldm+4pt1boldbqmCe …”
Section: Resultsmentioning
confidence: 99%
“…As a kind of crystalline material containing metal or metal cluster junctions, metal–organic skeleton materials are expected to become heterogeneous catalysts or catalyst carriers [113,114,115,116,117,118,119,120]. MOF materials provide a highly tunable platform for structure and performance, integrating all the properties required for catalysis, including high surface area, high porosity, active metal sites, recyclability, and high crystallinity [55,121,122,123,124].…”
Section: Application Of Mof/silica Compositementioning
confidence: 99%